The RELATION OF NEUTROPHIL ELASTASE LEVEL WITH TISSUE DESTRUCTION IN GINGIVITIS AND PERIODONTITIS: HUBUNGAN KADAR NEUTROFIL ELASTASE DENGAN KERUSAKAN JARINGAN PERIODONTAL PADA GINGIVITIS DAN PERIODONTITIS - Kasuma, Nila (Dentika: Dental Journal, 2017)
Periodontal disease consists of gingivitis and periodontitis. They occur due to the interaction between bacterial antigens and the host tissue hence neutrophil is activated, antibody is produced and bone resorption is occurred. Enzymatic changes to diagnose periodontal disease index (PDI) based on biomarker measurement scale is useful for an accurate diagnosis and a successful measurement of periodontal disease therapy. Gingival crevicular fluid (GCF) was selected as the biological medium. This research aims to analyze the relationship between neutrophil elastase level and periodontal tissue damages at gingivitis and periodontitis. The study involved 66 people as samples with 22 healthy samples, 22 mild gingivitis samples and 22 early periodontitis samples. Enzyme level studied was tested using ELISA technique. In this cross-sectional study, neutrophil elastase enzyme level was compared between healthy, mild gingivitis and early periodontitis sample groups. Data analysis was performed using ANOVA test. The average NE level based on PDI group is ± SD 2.65 ng/dl ± 1.28 in healthy sample group. There is an increase by 2.3 times in mild gingivitis sample group where NE level is ± SD 6.27 ng/dl ± 1.13.While, the light periodontitis group has NE level of ± SD 9.38 ng/dl ± 1.06 which equals to 3.5 times increase from the healthy sample group. This research concludes that the rise of neutrophil elastase level in gingival crevicular fluid is related to the severity of gingivitis and periodontitis diseases.